Slope structural health monitoring method against rainfall-induced shallow landslide. (October 2019) - Koizumi, K; Oda, K; Komatsu, M; Ito, S; Tsutsumi, H
Abstract: The structural health monitoring of a slope against rainfall-induced shallow landslides has become an important issue in Japan with the recent instances of extreme weather. In particular, the early detection of a sudden rainfall-induced shallow landslide is well known to be relatively difficult compared with that of a slow-moving landslide. Thus, local governments or civil-structure management companies provide residents or users with early warning information of a disaster via rainfall-based data. However, rainfall information is not enough to predict the risk of individual slope disasters because it does not directly reflect the soil-moisture condition of a slope. To solve this problem, a soil moisture-based index (iQS) is proposed. The applicability of iQS in a real slope was evaluated using the result obtained by monitoring a real slope during heavy rainfall along an expressway. The monitoring results of the real slope were seen to agree well with the results of past laboratory experiments. This implies that slope deformation owing to the rise in water level does not occur unless the volumetric water content exceeds the IQS of the real slope. Based on this result, iQS can be used for predicting the risk of shallow landslides at an early stage.